Using high frequency and low-intensity ultrasound to enhance activated sludge characteristics - Mohammadi, Parviz; Karami, Nasim; Zinatizadeh, Ali Akbar; Falahi, Farzaneh; Aghamohammadi, Nasrin; Almasi, Ali (Elsevier, 2019)
In this study, high-frequency ultrasound wave (1.8 MHz) at low intensity was applied to improve activated sludge settleability at high MLSS concentration. The effect of irradiation intensity, sonication mode, MLSS concentration and sample volume on the physical characteristics of sludge in a pilot scale settling column were investigated for optimizing the conditions. The obtained results showed that high-frequency ultrasound decreased the height of sludge (44%) and effluent turbidity (82.2%) and increased sludge settling velocity about 3 times at high biomass concentration. Irradiation intensity of 0.4 w/cm2 and sonication mode with interval times of 10 s showed the best results on the performance of the system at MLSS concentration of 8000 mg/L with a sample volume of 3 L. © 2019 Elsevier B.V.